Voter Partisanship and the Effect of Distributive Spending on Political Participation. Issue 1 (9th August 2012) - Chen, Jowei
<x xml:space="preserve">Abstract</x> Do distributive benefits increase voter participation? This article argues that the government delivery of distributive aid increases the incumbent party's turnout but decreases opposition‐party turnout. The theoretical intuition here is that an incumbent who delivers distributive benefits to the opposing party's voters partially mitigates these voters' ideological opposition to the incumbent, hence weakening their motivation to turn out and oust the incumbent. Analysis of individual‐level data on FEMA hurricane disaster aid awards in Florida, linked with voter‐turnout records from the 2002 (pre‐hurricane) and 2004 (post‐hurricane) elections, corroborates these predictions. Furthermore, the timing of the FEMA aid delivery determines its effect: aid delivered during the week just before the November 2004 election had especially large effects on voters, increasing the probability of Republican (incumbent party) turnout by 5.1% and decreasing Democratic (opposition party) turnout by 3.1%. But aid delivered immediately after the election had no effect on Election Day turnout.